Change in Coronary Blood Flow After Percutaneous Coronary Intervention in Relation to Baseline Lesion Physiology: Results of the JUSTIFY-PCI Study. (June 2015) - Nijjer, Sukhjinder S.; Petraco, Ricardo; van de Hoef, Tim P.; Sen, Sayan; van Lavieren, Martijn A.; Foale, Rodney A.; Meuwissen, Martijn; Broyd, Christopher; Echavarria-Pinto, Mauro; Al-Lamee, Rasha; Foin, Nicolas; Sethi, Amarjit; et al.
Abstract : Background—: Percutaneous coronary intervention (PCI) aims to increase coronary blood flow by relieving epicardial obstruction. However, no study has objectively confirmed this and assessed changes in flow over different phases of the cardiac cycle. We quantified the change in resting and hyperemic flow velocity after PCI in stenoses defined physiologically by fractional flow reserve and other parameters. Methods and Results—: Seventy-five stenoses (67 patients) underwent paired flow velocity assessment before and after PCI. Flow velocity was measured over the whole cardiac cycle and the wave-free period. Mean fractional flow reserve was 0.68±0.02. Pre-PCI, hyperemic flow velocity is diminished in stenoses classed as physiologically significant compared with those classed nonsignificant ( P <0.001). In significant stenoses, flow velocity over the resting wave-free period and hyperemic flow velocity did not differ statistically. After PCI, resting flow velocity over the wave-free period increased little (5.6±1.6 cm/s) and significantly less than hyperemic flow velocity (21.2±3 cm/s; P <0.01). The greatest increase in hyperemic flow velocity was observed when treating stenoses below physiological cut points; treating stenoses with fractional flow reserve ⩽0.80 gained Δ28.5±3.8 cm/s, whereas those fractional flow reserve >0.80 had a significantly smaller gain (Δ4.6±2.3 cm/s; P <0.001). The change in pressure-only physiological indices demonstrated a curvilinear relationship to the change in hyperemic flow velocity but was flat for resting flow velocity. Conclusions—: Pre-PCI physiology is strongly associated with post-PCI increase in hyperemic coronary flow velocity. Hyperemic flow velocity increases 6-fold more when stenoses classed as physiologically significant undergo PCI than when nonsignificant stenoses are treated. Resting flow velocity measured over the wave-free period changes at least 4-fold less than hyperemic flow velocity after PCI.